DIGITALISASI LAYANAN SURAT KETERANGAN PADA DESA LIU KABUPATEN WAJO - Faisal, Baso; Sahar, Nurman (Politeknik STIA LAN Makassar, 2024)
Certificate services for community needs in Liu Village are currently based on manual certificate production. People who want to obtain a certificate must go immediately to the village office and present the administrative prerequisites, which include a photocopy of their family or identity card. Manually delivering certificate services takes a lengthy time since errors frequently occur when carrying out administrative needs; also, technical problems frequently occur throughout the certificate service provisioning process. According to Law Number 25 of 2009 concerning Public Services, this prevents the provision of simple and quick services. The objective of this study was to digitize the certificate creation system using the web and Android-based SI-SUKET (Sistem Informasi Surat Keterangan) application. This study applied a descriptive qualitative approach. The data gathering process used in this study included observation, interviews, and document review. The output of this syudy are presented in the form of an application that can help village officials provide certificate-making services in Liu Village, Majauleng District, Wajo Regency.